Enhanced Cell Inactivation and Double-Strand Break Induction in V79 Chinese Hamster Cells by Monochromatic X-Rays at Phosphorus K-Shell Absorption Peak - Teruaki Konishi; Daichi Yoshihara; Munetoshi Maeda; Daisuke Ohsawa; Noriko Usami; Kotaro Hieda (Quantum Beam Science, 2020)
The cell inactivation and DNA double-strand break (DSB) induction by K-shell ionization of phosphorus atoms and Auger electrons were investigated. Monochromatic X-rays of on and below the phosphorus K-shell absorption peak, 2.153 keV and 2.147 keV were exposed to Chinese hamster lung fibroblast V79 cells. Survival fractions were plotted against exposure, Ψ [nC/kg] and the linear-quadratic model was adapted to estimate the parameters, α and β, of the survival curves. DSB induction rate [DSB/cell/Ψ] was estimated from the measured fractions of induced DNA fragments below 4.6 Mbp (Find(k < 4.6)), which were determined using pulse field gel electrophoresis. As results, cell inactivation and DSB induction rate of on the peak were significantly higher compared to that of the below. However, when converting Ψ to absorbed dose (Gy) of cell nucleus, the enhanced effect was only observed for parameter α, and not for a survival dose (Gy) of 37%, 10%, and 1% nor for a DSB induction rate. Our findings indicate that enhancement of cell inactivation and DSB induction were due to the additional dose delivered to the DNA and more complex DSB lesions were induced due to the release of phosphorus K-shell photoelectrons and Auger electrons.